2009
DOI: 10.1074/jbc.m805379200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β/Smad3 Signaling Regulates Insulin Gene Transcription and Pancreatic Islet β-Cell Function

Abstract: Pancreatic islet ␤-cell dysfunction is a signature feature of Type 2 diabetes pathogenesis. Consequently, knowledge of signals that regulate ␤-cell function is of immense clinical relevance. Transforming growth factor (TGF)-␤ signaling plays a critical role in pancreatic development although the role of this pathway in the adult pancreas is obscure. Here, we define an important role of the TGF-␤ pathway in regulation of insulin gene transcription and ␤-cell function. We identify insulin as a TGF-␤ target gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
155
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(171 citation statements)
references
References 55 publications
9
155
1
Order By: Relevance
“…Similarly, Glut2 was significantly decreased in Pdx1 + /Ins low immature beta cells [1]. Consistent with our findings, Glut2 was elevated in Smad3 knockout islets [38]. A strong reduction in Glut2 expression is an early indicator of beta cell stress and possibly dedifferentiation in many mouse models of glucose intolerance or diabetes [45], including mice with reduced Pdx1 [46].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, Glut2 was significantly decreased in Pdx1 + /Ins low immature beta cells [1]. Consistent with our findings, Glut2 was elevated in Smad3 knockout islets [38]. A strong reduction in Glut2 expression is an early indicator of beta cell stress and possibly dedifferentiation in many mouse models of glucose intolerance or diabetes [45], including mice with reduced Pdx1 [46].…”
Section: Discussionsupporting
confidence: 89%
“…Follistatin increased the expression of these genes. Consistent with these negative effects of activin A, the TGFβ/SMAD pathway is known to restrict pancreatic progenitor specification, in part by restraining Pdx1 expression during early embryonic development [37] genes and also that downregulation of Smad3 improved beta cell function [38]. Bone morphogenetic protein (BMP) signalling, also mediated via SMADs, prevented beta cell differentiation in zebrafish [39].…”
Section: Discussionmentioning
confidence: 93%
“…In line with our observation that Smad3 overexpression suppresses GSIS, a previous study reported that pancreatic islets isolated from Smad3 knockout mice showed enhanced insulin secretion in response to glucose as well as altered expression of several genes involved in beta cell function [38]. On the other hand, overexpression in adult islets of Smad7, which inhibits Smad signalling by all TGF-β superfamily proteins, has been shown to reduce GSIS by affecting islet insulin content and the expression of several key genes for beta cell function, such as Mafa and Menin (also known as Men1) [39].…”
Section: Discussionsupporting
confidence: 73%
“…Our results show that pancreatic islets in mice are affected by systemic aging, and aged mice exhibit age-dependent deterioration of glucose homeostasis, despite beta cells being fully competent in advanced age. In particular, aged mice were insulin-resistant and glucoseintolerant, although intolerance was only observed when aged mice were forced to release more insulin; for example, after a higher glucose load (37,38). Our results concur with those of several previous studies (3,5,6,39) but contrast with studies reporting insulin secretory defects with age (1,2,4,8).…”
Section: Discussioncontrasting
confidence: 57%